Analysis of Factor that Preferred by Customer in the Selection of Batara Savings Products at BTN Bank Branch Kamal - Moh Jufriyanto; Yudha Dwi Putra Negara; Doni Abdul Fatah (Universitas Trunojoyo Madura, 2020)
Factor analysis is a statistical analysis that tries to find a relationship (interrelationship) between a number of variables are mutually independent from one another, so that it can be made one or several sets of variables are less than the amount of the initial variables. Researchers want to conduct research on the factors that necessitated the customer in product selection god savings deposits at Bank BTN Kamal, Bangkalan by factor analysis approach. From the results in getting that formed five factors capable of representing on the seventeenth of the variables used factor analysis conducted, five factors formed can be seen from the eigen value more than 1 and pictures scree plot. Factors which is made by customers of Bank BTN in the selection of savings products Batara ie Employee Bank BTN responsive in serving, security transactions, procedures (and requirements) account opening Savings Batara easy was infested, Administration fee is low, and Employees of Bank BTN can give correct information and clear.